Measurements of W±Z production cross sections in pp collisions at √s = 8 TeV with the ATLAS detector and limits on anomalous gauge boson self-couplings - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physical review, 2016)
This paper presents measurements of W±Z production in pp collisions at a center-of-mass energy of 8 TeV. The gauge bosons are reconstructed using their leptonic decay modes into electrons and muons. The data were collected in 2012 by the ATLAS experiment at the Large Hadron Collider and correspond to an integrated luminosity of 20.3  fb−1. The measured inclusive cross section in the detector fiducial region is σW±Z→ℓ′νℓℓ=35.1±0.9(stat)±0.8(sys)±0.8(lumi)  fb, for one leptonic decay channel. In comparison, the next-to-leading-order Standard Model expectation is 30.0±2.1  fb. Cross sections for W+Z and W−Z production and their ratio are presented as well as differential cross sections for several kinematic observables. Limits on anomalous triple gauge boson couplings are derived from the transverse mass spectrum of the W±Z system. From the analysis of events with a W and a Z boson associated with two or more forward jets an upper limit at 95% confidence level on the W±Z scattering cross section of 0.63 fb, for each leptonic decay channel, is established, while the Standard Model prediction at next-to-leading order is 0.13±0.01  fb. Limits on anomalous quartic gauge boson couplings are also extracted.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, V. Radescu, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2831 weitere Personen]
Im Titel sind die Zeichen "+" und "-" hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 28.05.2020